The diversity and activity patterns of medium and large terrestrial mammals in the Talamanca Mountain Range, Costa Rica (UNED Research Journal, 2021)
Introduction: The Talamanca Range in the southeast of Costa Rica is a priority region for conservation, but its ecosystems and species are little known. The study of wild mammals can contribute to our understanding of the trophic structure and conservation needs of tropical forests, which are some of the most diverse ecosystems on the planet. Objective: To evaluate the species richness, relative abundance and activity patterns of medium and large mammals in La Amistad National Park and the Quetzal Tres Colinas Biological Corridor. Methods: Continuous monitoring was carried out from July 12, 2018 to April 18, 2021 using 18 photo-trapping stations, each consisting of a camera trap and a scent station. Results: Based on a sampling effort of 15 335 camera trap days, we obtained 36 667 records in which we detected 27 species of medium and large wild mammals, all of which are in one of the risk categories at the national or international level. The species with the widest distribution and the greatest relative abundance were Sciurus granatensis, Tapirus bairdii, Sylvilagus dicei and Mazama temama. The least abundant species, with the most restricted distribution, were Ateles geoffroyi, Cebus imitator and Microsciurus alfari. Five species were diurnal, six were nocturnal and crepuscular, and 14 species were cathemeral. The greatest species richness was found in the Premontane and Lower Montane zones, while the endemic species were in both of these zones and the Subalpine zone. Eight species had lunarphobia, six lunarphilia and six had no pattern. Conclusion: These areas protect important Premontane to Subalpine populations of medium-size and large terrestrial mammals, many cathemeral or with lunarphobia, and should continue to be monitored.
Keywords: Páramo; peat bog; cloud forest; life zone; altitudinal zone